Bipolar disorder - Strakowski, Stephen M. (Oxford American psychiatry library., 2014)
Bipolar disorder is one of the most common and disabling conditions affecting humankind. It is a leading cause of disability and mortality worldwide, affecting millions of people. The illness is complex and dynamic, so that many individuals are misdiagnosed for years and clinicians struggle with identifying the most appropriate and successful treatment. Because it is complex and common, people suffering from bipolar disorder seek help from clinicians of all types - from psychiatrists, family doctors, gynecologists, and internists to psychologists, social workers and other therapists. For clini.